Identification of 5-hydroxytryptamine receptor gene polymorphisms modulating hyperprolactinaemia in antipsychotic drug-treated patients with schizophrenia. (3rd April 2017) - Ivanova, Svetlana A.; Osmanova, Diana Z.; Freidin, Maxim B.; Fedorenko, Olga Yu; Boiko, Anastasia S.; Pozhidaev, Ivan V.; Semke, Arkadiy V.; Bokhan, Nikolay A.; Agarkov, Alexey A.; Wilffert, Bob; Loonen, Anton J.M.
Abstract: Objectives: Hyperprolactinaemia (HPRL) is a classical side effect of antipsychotic drugs primarily attributed to blockade of dopamine D2 subtype receptors in the pituitary gland. Although dopamine is considered the primary factor inhibiting prolactin release, the activity of prolactin-producing lactotrophs is also regulated by the secretagogues thyrotrophin releasing hormone, vasoactive intestinal polypeptide and serotonin (5-hydroxytryptamine; 5-HT). Methods: We describe the association between HPRL and a set of 29 SNPs from 5-HT receptor genes HTR1A, HTR1B, HTR2A, HTR2C, HTR3A, HTR3B and HTR6 in a population of 446 Caucasians (221 males/225 females) with a clinical diagnosis of schizophrenia (according to ICD-10: F20) who were treated with classical and/or atypical antipsychotic drugs. Results: None of the studied autosomal markers were found to be associated with HPRL. However, a significant association was established between various HTR2C polymorphisms and HPRL. Conclusions: This study revealed an association between HPRL and X-chromosome haplotypes comprised of the rs569959 and rs17326429 polymorphisms.